BRINGING SERBIA/SCG CLOSER TO THE EUROPEAN UNION - current agricultural and agrarian policy comparisons- - Milanovic, Milan R. (Economics of Agriculture, 2006)
In the years ahead, the European perspective of Serbia/Serbia and Montenegro shall be observed and tested through the Stabilisation and Association Process, initiated by the EU for the countries of the Western Balkans. The Process (initiated for Serbia and Montenegro in October 2005), apart for the political, security and other aspects, implies significant adjustments and the transformation of the overall economic system. Agriculture, that is, agrarian-economic structure and the agrarian policy, is one of the most important but at the same time one of the most sensitive sectors. This paper is trying to answer the following questions in the light of new perspectives and comparisons – is Serbia/Serbia and Montenegro moving towards Europe, and at what pace; to what extent are agrarian structure and agrarian policy (in)compatible with the European processes and standards and what are the crucial problems in this sector that need to be solved on the path towards Europe.